G49 Teaching new nursing staff how to raise concerns using the pace approach and high-fidelity simulation. (24th May 2017) - Junk, C; McNaughten, B; Diamond, C; Bourke, TW; Thompson, AJ
Abstract : Aims: Hierarchy and leadership are essential within any multidisciplinary team. However, to err is human and team leaders can make mistakes irrespective of seniority. It is important that everyone within the team feels confident in raising concerns to ensure patient safety. This can be particularly challenging for new staff joining established healthcare teams. The Advanced Paediatric Life Support (APLS) Group recommend the PACE approach as a structured method for raising concerns. We aimed to improve the confidence of new children's nursing staff in raising concerns by introducing teaching on this topic into their induction simulation session. Methods: New nurses undertook a simulated clinical scenario in which the doctor was deliberately hesitant and reluctant to administer appropriate treatment. Teaching was then provided on the PACE approach. Each nurse then participated again in a similar scenario. Using pre and post questionnaires we asked the 23 participants to suggest on a Likert scale how confident they would feel in challenging a nursing colleague or doctor if they had concerns about their practice before and after the session. During the debrief of the first scenarios we asked participants how they had felt. Results: There was no difference in participants' confidence between challenging a nurse or doctor (3.4/5) prior to training. Following the initial scenario the nurses reported feeling ' frustrated ' and ' scared ' . One stated ' this is my worst fear. ' After the PACE teaching and subsequent scenarios nursing staff stated that their confidence in challenging nurses and doctors had increased to 4.3/5 and 4.2/5 respectively. Free text comments included: 'Hearing from doctors that they would rather be challenged was reassuring.' 'Improved my confidence to speak up when querying a decision' Conclusion: Nursing staff reported improved confidence in their ability to raise concerns. This can only serve to improve patient safety. We have subsequently embedded PACE training within all our medical and nursing induction programmes.